ANALISIS KESALAHAN KEBAHASAAN DALAM PENULISAN KARYA TULIS ILMIAH - Aurelia Sakti Yani; Restu Bias Primandhika (IKIP Siliwangi, 2023)
The purpose of this study is to describe: (1) Indonesian errors in scientific papers, (2) factors causing errors (3) solutions to minimize language errors. This research is qualitative descriptive research with a sample of scientific papers of level 1 students. Purposive sampling techniques are used to obtain research data as well as through interview and document analysis. The interactive analysis model is used as a data analysis technique, this technique includes four components, namely data collection, data reduction, data presentation, and verification. The results that can be concluded from this study are 1) there are errors at the linguistic level which include 65% errors in the field of morphology, 20% errors in the field on syntax and 15% errors in the field of semantic 2) factors that cause these errors, namely students inaccuracy in heading linguistic rules, lack of understanding of student and ineffective ways of delivering material by lecturers 3) the solution to overcome these language errors is to increase the accuracy of students and lectures using teaching materials that can increase student motivation in learning.